2008
DOI: 10.1097/inf.0b013e31815988ed
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Malaria in African Children

Abstract: These findings delineate the patterns of severe malaria in children in a West African mesoendemic urban setting. They validate practicable prognostic indicators of life-threatening malaria for use in the limited facilities available in African health centers and provide a frame of reference for further research addressing life-threatening malaria in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
2
18
0
1
Order By: Relevance
“…Malian children with CM were recruited as described previously (14)(15)(16)(17). The children with CM were hospitalized between 1999 and 2003 in the pediatric department of the Gabriel Toure Hospital in Bamako (Mali).…”
Section: Methodsmentioning
confidence: 99%
“…Malian children with CM were recruited as described previously (14)(15)(16)(17). The children with CM were hospitalized between 1999 and 2003 in the pediatric department of the Gabriel Toure Hospital in Bamako (Mali).…”
Section: Methodsmentioning
confidence: 99%
“…This study included 341 children with SM (either CM or SA) and 42 children with uncomplicated malaria (UM) ( Table 1) hospitalized in the pediatric department of Gabriel Toure Hospital in Bamako, Mali [17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…(WHO 2004) A reduction in the frequency of severe anaemia beyond 24 months of life with a two fold increase in prevalence of cerebral malaria across same age band had earlier been reported in Ghana and Mali. (Oduro et al, 2007, Ranque et al, 2008 The fact that most cases of severe anaemia are seen in children less than 2years of age is attributable to the smaller red cell mass and the relatively lower immunity to the malaria parasite compared to the older children. (Newton & Krishna, 1998) This study demonstrated a progressive and consistent reduction in proportion of severe malaria anaemia with increasing age supporting the assertion that repeated exposure to malaria with advancing age increased acquired immunity to the parasite with a reduction in severity of malaria presentation.…”
Section: Discussionmentioning
confidence: 99%